1985
DOI: 10.1007/bf00006613
|View full text |Cite
|
Sign up to set email alerts
|

Benthic community metabolism in four temperate stream systems: An inter-biome comparison and evaluation of the river continuum concept

Abstract: Benthic community metabolism was studied on four stream systems located in different biomes in the United States: the eastern deciduous forest (Pennsylvania, PA, and Michigan, MI), the high desert (Idaho, ID), and the coniferous forest (Oregon, OR). Studies were designed to test the hypothesis advanced within the River Continuum Concept that a transition in community metabolism will occur from a predominance of heterotrophy in headwaters to a predominance of autotrophy in mid-sized reaches, with a return to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
186
6
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(212 citation statements)
references
References 69 publications
18
186
6
2
Order By: Relevance
“…This result is similar to other studies of forested streams (Minshall et al 1983, Naiman 1983, Bott et al 1985; however, metabolism in grassland rivers has generally indicated little longitudinal trend in net metabolism because of high GPP in upstream river reaches where there is no gallery forest (Wiley et al 1990, Young andHuryn 1996). Meyer and Edwards (1990) suggested that NEP was a more useful indicator of organic matter transitions than P/R when considering C budgets in stream systems because NEP demonstrates the amount of C deficit or surplus.…”
Section: Longitudinal Trends In Metabolismsupporting
confidence: 87%
See 3 more Smart Citations
“…This result is similar to other studies of forested streams (Minshall et al 1983, Naiman 1983, Bott et al 1985; however, metabolism in grassland rivers has generally indicated little longitudinal trend in net metabolism because of high GPP in upstream river reaches where there is no gallery forest (Wiley et al 1990, Young andHuryn 1996). Meyer and Edwards (1990) suggested that NEP was a more useful indicator of organic matter transitions than P/R when considering C budgets in stream systems because NEP demonstrates the amount of C deficit or surplus.…”
Section: Longitudinal Trends In Metabolismsupporting
confidence: 87%
“…Walker Camp Prong, in the Great Smoky Mountain National Park, Tennessee, had the lowest NPP of streams compared here (Mulholland et al 1986). Although NPP at our upstream sites was low, our downstream sites had NPP values that were higher than other eastern US streams (Hoskin 1959, Hornberger et al 1977, Sumner and Fisher 1979, Hill and Webster 1982, Bott et al 1985 but lower than streams from the midwest (Bott et al 1985, Wiley et al 1990). NPP at our most downstream site was very similar to the New River, Virginia, another mid-sized southern Appalachian river (Hill and Webster 1982).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Heterotrophic state was considerably less variable, ranging about 10-fold with the central one third of the distribution falling between 6.7 and 8.3 g O 2 m ÏȘ2 d ÏȘ1 (Table 5). Bott et al (1985) reviewed studies of Ïł70 streams with Fig. 2.…”
Section: Determining Boundaries Of Trophic Statementioning
confidence: 99%